FULFILLING THE CHILD WELFARE ON THE SPIRITUAL ASPECT AT THE CHILDREN CORRECTIONAL INSTITUTION - Welly, Irma; Rukminto Adi, Isbandi; Achjani Zulfa, Eva (The Islamic Education and Multiculturalism Foundation, 2023)
Fulfillment of the welfare of children in conflict with the law (ABH) in the spiritual aspect is to changes in behavior of the of children in conflict with the law who are undergoing coaching at the Child Correctional Institution (LPKA). The target of fulfilling the spiritual aspect is increasing religious knowledge and the practice of worship. The purpose of this study was to analyze the fulfillment of the welfare of children in conflict with the law related to spiritual needs in Child Correctional Institute (LPKA) Bandung, Palembang and Tangerang. This study uses a qualitative approach with explanatory research. This study also used a purposive sampling technique. As for the data collection conducted by researchers, namely in-depth interviews, observation and documentation studies. The results of the research explore the spiritual condition of children in conflict with the law, the efforts made, and the existence of risk factors and protective factors that affect children at the micro system level. Changes in the behavior of children are being able to carry out worship even though the implementation of worship is carried out because of obligation not because of their own awareness, children carry out worship because of their own awareness that they get from training. Another change is that children have the initiative to carry out other acts of worship such as reading the Quran before prayer, performing midnight prayers at night.